2001
DOI: 10.4049/jimmunol.167.7.3858
|View full text |Cite
|
Sign up to set email alerts
|

A Novel, Nonclassical MHC Class I Molecule Specific to the Common Chimpanzee

Abstract: All expressed human MHC class I genes (HLA-A, -B, -C, -E, -F, and -G) have functional orthologues in the MHC of the common chimpanzee (Pan troglodytes). In contrast, a nonclassical MHC class I gene discovered in the chimpanzee is not present in humans or the other African ape species. In exons and more so in introns, this Patr-AL gene is similar to the expressed A locus in the orangutan, Popy-A, suggesting they are orthologous. Patr-AL/Popy-A last shared a common ancestor with the classical MHC-A locus &gt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 63 publications
2
53
0
Order By: Relevance
“…The Mamu-A*05͞*24 locus (proposed name Mamu-A2), characterized by differential distribution, might encode a nonclassical class I protein with a specialized function in the immune response. A similar situation may exist for the Patr-AL locus in chimpanzees (30).…”
Section: Resultsmentioning
confidence: 89%
“…The Mamu-A*05͞*24 locus (proposed name Mamu-A2), characterized by differential distribution, might encode a nonclassical class I protein with a specialized function in the immune response. A similar situation may exist for the Patr-AL locus in chimpanzees (30).…”
Section: Resultsmentioning
confidence: 89%
“…Although Popy-E and -G may indeed represent orthologs of the human genes, the properties of Popy-A, -B, and -C imply less straightforward, paralogous relationships. Popy-A appears less related to HLA-A and Patr-A than to Patr-AL, a nonclassical class I gene present on some chimpanzee MHC haplotypes (15). Unlike HLA-A or Patr-A, which are fixed, Popy-C is present on ϳ50% of Popy-MHC haplotypes (14); but in contrast, Popy-B appears duplicated such that individual orangutans express three or four Popy-B alleles (14,44).…”
Section: Discussionmentioning
confidence: 99%
“…Being more divergent from humans than the chimpanzee, the orangutan has an MHC in which the class I genes have several defined differences from their human counterparts (11). Whereas Popy-E and -G are orthologous (12,13), the Popy-A and -B genes may not be orthologs of HLA-A and -B (14,15). Most important is that the Popy-C locus is only present on ϳ50% of MHC haplotypes; and thus, a significant minority of orangutans lack an MHC-C locus (14).…”
mentioning
confidence: 99%
“…Comparative analysis of a single gorilla MHC haplotype showed that Gogo-Oko is syntenic to the chimpanzee A -related locus Patr-AL (Gleimer et al 2011). Patr-AL is present on only half of the surveyed chimpanzee MHC haplotypes and is in strong linkage disequilibrium with Patr-A , the chimpanzee orthologue of HLA-A (Adams et al 2001; Geller et al 2002). In contrast, the gorilla MHC haplotype with Gogo-Oko lacks the genomic block containing the A locus (Gleimer et al 2011).…”
Section: Introductionmentioning
confidence: 99%